2002
DOI: 10.1097/00004647-200201000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Myeloperoxidase Increases Infarct Volume and Nitrotyrosine Formation in Mouse Brain

Abstract: Peroxynitrite is responsible for nitration in vivo, whereas myeloperoxidase can also catalyze protein nitration in the presence of high NO2(-) levels. Recent reports of myeloperoxidase-mediated enzyme inactivation or lipid peroxidation have suggested a role of myeloperoxidase in various pathological conditions. To clarify the role of myeloperoxidase in ischemic brain injury, the authors measured nitrotyrosine formation and infarct volume in myeloperoxidase-deficient or wild-type mice subjected to 2-hour focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…4-6). Tyrosine nitration is involved in many postischemic modifications [55][56][57]. Examples of proteins susceptible to inactivation by tyrosine nitration include mitochondrial superoxide dismutase [58,59] and several enzymes involved in oxidative energy metabolism, including aconitase [60], glutamate dehydrogenase [46], α-ketoglutarate dehydrogenase [61], and PDHC [46].…”
Section: Discussionmentioning
confidence: 99%
“…4-6). Tyrosine nitration is involved in many postischemic modifications [55][56][57]. Examples of proteins susceptible to inactivation by tyrosine nitration include mitochondrial superoxide dismutase [58,59] and several enzymes involved in oxidative energy metabolism, including aconitase [60], glutamate dehydrogenase [46], α-ketoglutarate dehydrogenase [61], and PDHC [46].…”
Section: Discussionmentioning
confidence: 99%
“…3) and MPO (data not shown) generate NT from NO͞O 2 Ϫ , but only after conversion of each reactant to NO 2 Ϫ and H 2 O 2 , respectively. Although peroxidases unmistakably account for significant amounts of NT formation in vivo, this mechanism may not adequately explain the nitrated proteins detected in a MPO Ϫ/Ϫ mouse model (25) or under acute pathologic conditions void of inflammatory cells, such as ischemia reperfusion injury to the brain (51). Brennan et al (50) have recently shown, using an EPO Ϫ/Ϫ ͞MPO Ϫ/Ϫ mouse inflammatory model, that leukocyte peroxidase-dependant formation of the peroxidase activity markers bromo-and chloro-tyrosine does not necessarily parallel formation of NT.…”
Section: Discussionmentioning
confidence: 99%
“…Although leukocyte peroxidases likely account for a substantial amount of NT production in vivo, this mechanism fails to explain NT formation in the absence of inflammatory cells or peroxidases [i.e., a MPO Ϫ/Ϫ mouse model (25)]. …”
mentioning
confidence: 99%
“…MPO-mediated radicalization of molecules induces apoptosis (7) and nitro-tyrosination of proteins (8). Therefore, MPO is a key component of inflammation and has been shown to play a major role in animal models of stroke in the posthypoxic inflammatory response (9,10). In human cerebral ischemia, certain MPO genotypes are associated with increased brain infarct size and poorer functional outcome (11).…”
mentioning
confidence: 99%